171k views
1 vote
Solve for x in the equation.

Solve for x in the equation.-example-1

1 Answer

1 vote

Answer:

The solution is
\displaystyle x=1\pm √(47). Fourth option

Step-by-step explanation:

Solve for x:


2x^2+3x-7=x^2+5x+39

Move all the terms from the right to the left side of the equation, a zero in the right side:


2x^2+3x-7-x^2-5x-39=0

Join all like terms:


x^2-2x-46=0

The general form of the quadratic equation is:


ax^2+bx+c=0

Solve the quadratic equation by using the formula:


\displaystyle x=(-b\pm √(b^2-4ac))/(2a)

In our equation: a=1, b=-2, c=-46

Substituting into the formula:


\displaystyle x=(-(-2)\pm √((-2)^2-4(1)(-46)))/(2(1))


\displaystyle x=(2\pm √(4+184))/(2)


\displaystyle x=(2\pm √(188))/(2)

Since 188=4*47


\displaystyle x=(2\pm √(4*47))/(2)

Take the square root of 4:


\displaystyle x=(2\pm 2√(47))/(2)

Divide by 2:


\displaystyle x=1\pm √(47)

First option: Incorrect. The answer does not match

Second option: Incorrect. The answer does not match

Third option: Incorrect. The answer does not match

Fourth option: Correct. The answer matches exactly this option

User Joachim Jablon
by
4.2k points